Design and analysis of a novel fair payment protocol in mobile environments - LIU Xia1; GU Tian-long1; DONG Rong-sheng1; GUO Yun-chuan1 (Tongxin xuebao)
A novel fair payment protocol in mobile environments was presented,which combined the payment protocols in fixed networks and considered the characteristics of mobile devices and wireless networks.The protocol was analyzed by model checker and compared with other payment protocols.The results show that the novel protocol has fairness,con-fidentiality and high efficiency and it is suitable for mobile environments.